PENGARUH EFEKTIVITAS SISTEM AUDIT INTERNAL TERHADAP KINERJA KEUANGAN BANK SYARIAH - Rifki Anggriana, Alvy; Risanto, Wawan; Edirianto, Sunardi (Program Studi Akuntansi Universitas Panca Bhakti, 2025)
The rapid development of Islamic banks in Indonesia shows the high level of public trust in the sharia-based financial system which is believed to be free from usury and in accordance with Islamic principles. However, some people still doubt the implementation of sharia in general in Islamic banks, especially regarding accountability and audit systems which are considered to still adopt conventional patterns. Internal audit and supervision of the Sharia Supervisory Board (DPS) play an important role in maintaining the effectiveness of internal control, increasing transparency, and ensuring compliance with sharia principles. The financial performance of Islamic banks is evaluated using indicators such as ROA, ROE, BOPO, FDR, and CAR, as well as measurements based on Maqasid Sharia. This study uses a descriptive qualitative method through a literature review to analyze the role of internal audit and internal control in preventing accounting fraud and supporting good corporate governance in Islamic banks in Indonesia. Keywords: Islamic Bank, Internal Audit, Financial Performance